2012
DOI: 10.1002/smi.2465
|View full text |Cite
|
Sign up to set email alerts
|

College Student Stressors: A Review of the Qualitative Research

Abstract: A total of 40 qualitative studies were reviewed and coded according to the college student stressors they represented. These studies utilized a variety of qualitative methods to examine stressors representing the following themes: relationships, lack of resources, academics, the environment, expectations, diversity, transitions and other stressors. Relationship stressors were the most commonly reported theme and covered areas including stress associated with family, romantic, peer and faculty relationships. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
155
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(167 citation statements)
references
References 75 publications
6
155
1
5
Order By: Relevance
“…This has been confirmed by some studies (Verger et al, 2009) although others have pointed out that relationships (between students) are the main source of stress for students (Hurst, Baranik, & Daniel, 2013). In our study, the perceived high level of intimidation of students by lecturers was a prominent study-related stressor.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…This has been confirmed by some studies (Verger et al, 2009) although others have pointed out that relationships (between students) are the main source of stress for students (Hurst, Baranik, & Daniel, 2013). In our study, the perceived high level of intimidation of students by lecturers was a prominent study-related stressor.…”
Section: Resultsmentioning
confidence: 60%
“…In our study, students reported experiencing stress because their parents expected them to complete their studies on time and become independent. The study by Hurst, (Hurst et al, 2013) indicates that expectations of the students themselves, striving for perfection, created stress. Again, sources for stress also play out as potential coping mechanisms (Eriksson & Lindström, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The significant stress factors that have been identified are: increased levels of studyrelated stress, students' financial situations, family problems, the problems ensuing from combining study and work, and those related to making the transition from home to university (Calvete & Connor-Smith, 2006;Cassidy, 2004;De Hoog, & Schilp, 2012;Hall, Chipperfield, Perry, Ruthig, & Goetz, 2006;Hurst, Baranik, & Daniel, 2013;Jessop, Herberts, & Solomon, 2005;Orr, Gwosc, & Netz, 2011;Robotham, 2008;Robotham & Julian, 2006;Schmidt & Simons, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Table 7. Other Services that would benefit College Athletes 46 managing academic stress, transitioning to a life of independence, and learning how best to navigate new environments (Hurst, Baranik, & Daniel, 2013;Lester, 2014).…”
mentioning
confidence: 99%